Characterization of a new murine cell line of sarcomatoid hepatocellular carcinoma and its application for biomarker/therapy development - Chia-Hung Yen (Nature Portfolio, 2017)
Abstract Sarcomatoid hepatocellular carcinoma (SHC) is a rare type of HCC with significantly poorer survival than ordinary HCC. Little is known about the mechanism associated with SHC and its biomarkers and therapy. Here, we established a mouse liver cancer cell line and designated as Ymac-1. A sarcomatous appearance was observed in the allograft tumor arose from Ymac-1. Liver-secreted plasma proteins were found in Ymac-1 cultured supernatant by proteomics analysis. The positive staining of CK7, CK8, Vimentin and the suppressed expression of AFP indicated that Ymac-1 is a SHC cell line. Compared to its original tumor, an elevated level of EMT markers, N-cadherin and Vimentin, was found in Ymac-1. Ymac-1 displayed a higher migration rate and side population percentage than a mouse ordinary HCC cell line-Hepa1-6. Microarray analysis was performed to identify potential biomarkers/therapeutic targets for SHC. G6pd, a vital enzyme in pentose phosphate pathway, is highly expressed in Ymac-1. Depletion of G6pd in Ymac-1 reduced CD133 expression and sphere formation. Positive correlations between G6PD and CD133 were observed in human specimen. Higher expression of both G6PD and CD133 in tumor were associated with poor survival. In summary Ymac-1 can be a useful SHC cell model for novel biomarker and therapy development.